Elementary Technical Mathematics

Published by Brooks Cole
ISBN 10: 1285199197
ISBN 13: 978-1-28519-919-1

Chapter 6 - Section 6.3 - Equations with Parentheses - Exercises: 49

Answer

y=-3

Work Step by Step

Simplifying 12 + 8(2y + 3) = (y + 7) + -16 Reorder the terms: 12 + 8(3 + 2y) = (y + 7) + -16 12 + (3 * 8 + 2y * 8) = (y + 7) + -16 12 + (24 + 16y) = (y + 7) + -16 Combine like terms: 12 + 24 = 36 36 + 16y = (y + 7) + -16 Reorder the terms: 36 + 16y = (7 + y) + -16 Remove parenthesis around (7 + y) 36 + 16y = 7 + y + -16 Reorder the terms: 36 + 16y = 7 + -16 + y Combine like terms: 7 + -16 = -9 36 + 16y = -9 + y Solving 36 + 16y = -9 + y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-1y' to each side of the equation. 36 + 16y + -1y = -9 + y + -1y Combine like terms: 16y + -1y = 15y 36 + 15y = -9 + y + -1y Combine like terms: y + -1y = 0 36 + 15y = -9 + 0 36 + 15y = -9 Add '-36' to each side of the equation. 36 + -36 + 15y = -9 + -36 Combine like terms: 36 + -36 = 0 0 + 15y = -9 + -36 15y = -9 + -36 Combine like terms: -9 + -36 = -45 15y = -45 Divide each side by '15'. y = -3 Simplifying y = -3
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.